European Ultrahigh‐Field Imaging Network for Neurodegenerative Diseases (EUFIND). Issue 1 (31st July 2019) - Düzel, Emrah; Acosta‐Cabronero, Julio; Berron, David; Biessels, Geert Jan; Björkman‐Burtscher, Isabella; Bottlaender, Michel; Bowtell, Richard; Buchem, Mark v; Cardenas‐Blanco, Arturo; Boumezbeur, Fawzi; Chan, Dennis; Clare, Stuart; et al.
Abstract: Introduction: The goal of European Ultrahigh‐Field Imaging Network in Neurodegenerative Diseases (EUFIND) is to identify opportunities and challenges of 7 Tesla (7T) MRI for clinical and research applications in neurodegeneration. EUFIND comprises 22 European and one US site, including over 50 MRI and dementia experts as well as neuroscientists. Methods: EUFIND combined consensus workshops and data sharing for multisite analysis, focusing on 7 core topics: clinical applications/clinical research, highest resolution anatomy, functional imaging, vascular systems/vascular pathology, iron mapping and neuropathology detection, spectroscopy, and quality assurance. Across these topics, EUFIND considered standard operating procedures, safety, and multivendor harmonization. Results: The clinical and research opportunities and challenges of 7T MRI in each subtopic are set out as a roadmap. Specific MRI sequences for each subtopic were implemented in a pilot study presented in this report. Results show that a large multisite 7T imaging network with highly advanced and harmonized imaging sequences is feasible and may enable future multicentre ultrahigh‐field MRI studies and clinical trials. Discussion: The EUFIND network can be a major driver for advancing clinical neuroimaging research using 7T and for identifying use‐cases for clinical applications in neurodegeneration.